Field potential recording from rat hippocampus provides a functional evaluation method for assessing demyelination and myelin repair. (1st October 2013) - Azin, Mahdieh; Goudarzvand, Mahdi; Mirnajafi-Zadeh, Javad; Javan, Mohammad
<x xml:space="preserve">Abstract</x> Objectives: In multiple sclerosis (MS) demyelination occurs in both white and gray matter. Here we introduce an electrophysiological approach for studying functional demyelination and myelin repair in rat hippocampus, a gray matter structure, which is frequently affected in patients suffering from MS. Methods: Using a stereotaxic approach, bipolar stimulating and monopolar recording electrodes were respectively implanted into the perforant path and the dentate gyrus of the hippocampus of the adult male Sprague-Dawley rats weighing 280-320 g. Animals received intra-hippocampal injections of saline or lysolecithin (LPC) and afterward, changes in the parameters of field potentials recorded from the dentate gyrus granular cells in response to electrical stimulation of perforant path were investigated on days 7, 14, and 28, post-lesion. Changes in the electrophysiological parameters were compared with changes in the molecular markers of myelination (myelin basic protein, MBP) and repairing cells (Olig2). Results: On day 2, a significant decrease in the slope of the population excitatory postsynaptic potential (pEPSP) and the amplitude of population spike (PS) was observed. However, during days 7-28, these parameters were increased toward control. Decreased expression of MBP and increased expression of Olig2 were observed on days 2 and 7 while the expression levels were partially reversed toward control on day 28. Discussion: Our data showed the efficacy of field potential recording for studying demyelination and endogenous myelin repair in hippocampus. Changes in electrophysiological parameters were concomitant with the level of molecular markers. This recording method provides an opportunity for functional evaluation of myelin loss and repair and the effect of potential therapies.